MOGIGU (MENGGOSOK GIGI ASYIK DENGAN LAGU) TO INCREASE BRUSHING TEETH OF THE ELEMENTARY SCHOOL - Diyah Fatmasari; Rasipin Rasipin; Bedjo Santoso; Supriyana Supriyana; Wahyu Jati Dyah Utami (Journal of Applied Health Management and Technology, 2019)
Tooth brushing programs that have been carried out in schools have not been able to change the brushing behavior of elementary school students, shown by OHI-S value = 1.3; DMF-T=1.09, def-t=1.78. Program improvement in behavioral aspects needs to be done to improve the dental health level of elementary school students. Behavioral changes are influenced by information. Information will be stored as much as 20% if delivered through visuals, 50% of the cost is delivered through audiovisual media and 70% if implemented in real practice.  Analyze the effectiveness of the audiovisual media model on tooth brushing habits of schoolchildren Method is Quasy experiment with pretest and posttest with control group design. The sample was divided into 2 groups, the audiovisual model in the intervention group, and the brushing program in the control group. The treatment was carried out for 21 days, the measurements were carried out pre-experiment, 25th and 35th days. Data were tested using the test freedman post hoc Wilcoxon, Man Whitney repeated, and Kruskal.  On the 25th-day measurement of significant changes in variable ways, long brushing teeth p0.05. At the 35th day measurement, there was a significant change in the method variable, morning brushing teeth p0.05. This model is effective against the formation of the habit of brushing teeth indicated by p0.001. Mogigu  model’s has the potential as an alternative to brush your teeth together in school so that it can be applied in the School Dental Health Business.